Community Treatment Orders and Supported Decision-Making - Brophy, Lisa; Kokanovic, Renata; Flore, Jacinthe; McSherry, Bernadette; Herrman, Helen (Frontiers in Psychiatry, 2019)
This paper presents findings from an interdisciplinary project undertaken in Victoria, Australia investigating the barriers and facilitators to supported decision-making (SDM) for people living with diagnoses including schizophrenia, psychosis, bipolar disorder and severe depression; family members supporting them and mental health practitioners, including psychiatrists. We considered how SDM can be used to align Australian laws and practice with international human rights obligations. The project examined the experiences, views and preferences of consumers of mental health services, including people with experiences of being on Community Treatment Orders (CTOs), in relation to enabling SDM in mental health service delivery. It also examined the perspectives of informal family members or carers and mental health practitioners. Victoria currently has high rates of use of CTOs and the emphasis on SDM in the Mental Health Act, 2014, is proposed as one method for reducing coercion within the mental health system and working towards more recovery-oriented practice. Our findings cautiously suggest that SDM may contribute to reducing the use of CTOs, encouraging less use of coercive practices and improving the experience of people who are subject to these orders, through greater respect for their views and preferences. Nonetheless,the participants in our study expressed an often-ambivalent stance towards CTOs. In particular, the emphasis on medication as the primary treatment option and the limited communication about distressing side effects, alongside lack choice of medication, was a primary source of concern. Fears, particularly among staff, about the risk of harm to self and others, and stigma attached to complex mental health conditions experienced by consumers and their families, represent important overarching concerns in the implementation of CTOs. Supporting the decision making of people on CTOs, respecting their views and preferences about treatment and moving towards reducing the use of CTOs require system-wide transformation and a significant shift in values and practice across mental health service delivery.